2021
DOI: 10.1186/s12906-021-03281-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of complementary and alternative medicine use in the general population of Babol, North of Iran, 2018

Abstract: Background Complementary and Alternative Medicine (CAM) have recently become more popular and accepted worldwide. One principal step to identify the status and organize strategies of CAM is evaluating the manner and the prevalence of its usage among people. This study aimed to investigate the prevalence of CAM modalities usage by the people of Babol, a central city in the North of Iran, in 2018. Methods Using the original International CAM Question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Moeini et al‘s study revealed that although 71.65% of the normal population of Babol, a Northern city in Iran, had used complementary and alternative medicine throughout their lives, only 6.21% of them visited a complementary medicine therapist to receive these medications. In addition, they demonstrated that herbal remedies were the most common complementary medicine (58.30%) among the normal population in Babol [ 29 ]. Furthermore, Montazeri et al reported that only about one-third of the patients who suffered cancer in Tehran, Iran, used complementary and alternative medicine for their disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moeini et al‘s study revealed that although 71.65% of the normal population of Babol, a Northern city in Iran, had used complementary and alternative medicine throughout their lives, only 6.21% of them visited a complementary medicine therapist to receive these medications. In addition, they demonstrated that herbal remedies were the most common complementary medicine (58.30%) among the normal population in Babol [ 29 ]. Furthermore, Montazeri et al reported that only about one-third of the patients who suffered cancer in Tehran, Iran, used complementary and alternative medicine for their disease.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Babol, a central city in northern Iran, has revealed that the CAM methods most frequently applied include herbal medicine, traditional medicine, homeopathy, chiropractic treatment, acupuncture, reflexology, and massage [15]. In Europe, the methods mostly applied are herbal medicine, homeopathy, chiropractic treatments, and acupuncture [16].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Babol, a central city in northern Iran, has revealed that the CAM methods most frequently applied include herbal medicine, traditional medicine, homeopathy, chiropractic treatment, acupuncture, re exology, and massage [15]. In Europe, the methods most applied are herbal medicine, homeopathy, chiropractic treatments, and acupuncture [16].…”
Section: Many Patients Do Not Admit That They Use Cam the Available S...mentioning
confidence: 99%